2004
DOI: 10.1007/s11172-005-0077-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cationic ruthenium diphosphine complexes with nido-dicarbaundecaborate anions. Molecular structure of [RuCl(dppe)2]+[7,8-nido-C2B9H12]−

Abstract: In metallacarborane chemistry, 16 and/or 18 elec tron cationic complexes of the general formula [M(L,L´) n ] + [7 R´ 8 R″ 7,8 nido C 2 B 9 H 10 ] -(M = Rh; R´ and R″ = H, Alk, Ar, PhS, PPh 2 ; L and L´ = P(Alk) 3 , PPh 3 , P(Alk)Ph 2 , etc., n = 3 or 4; M = Ir, R´, R″ = H; L = η 4 COD, L´ = (PAr 3 ) 2 , n = 0) have been represented earlier only by rhodium 1,2 and iridium 3 compounds. The only salt of this type with the complex nido carborane anion, [Rh(PPh 3 ) 3 ] + [7 {(1´ (closo 1´,2´ C 2 B 10 H 11 )} 7,8 ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…The second reaction product was eluted from the column by more polar CH 2 Cl 2 , which was removed in vacuo to give 0.05 g (11%) of complex 6. The data of 1 H, 31 P{ 1 H}, and 11 B NMR spectra of complex 6 fully coincided with the published data, 24 . The structure was solved by the direct method and refined by the full matrix least squares method on F 2 hkl with anisotropic ther mal parameters for all nonhydrogen atoms.…”
Section: Methodssupporting
confidence: 87%
“…The second reaction product was eluted from the column by more polar CH 2 Cl 2 , which was removed in vacuo to give 0.05 g (11%) of complex 6. The data of 1 H, 31 P{ 1 H}, and 11 B NMR spectra of complex 6 fully coincided with the published data, 24 . The structure was solved by the direct method and refined by the full matrix least squares method on F 2 hkl with anisotropic ther mal parameters for all nonhydrogen atoms.…”
Section: Methodssupporting
confidence: 87%
“…These compounds were found to display high catalytic activity in the cyclopropanation reactions of alkenes and dienes [3], and they can be used as the versatile building-block reagents in the construction of mono-and/or low-nuclearity metallacarboranes of different types and structures [4]. Recently, we have found that the PPh 3 groups in 6, P) 2 Ru}-5,6,10-l-(H) 3 -10-H-7,8-R 2 -7,8-C 2 B 9 H 6 ] (1, R = H; 2, R = Me) can easily be replaced by chelating diphosphines such as dppe or dppp in the course of the room-temperature displacement reaction in benzene affording stable cationic salts [RuCl{Ph 2 P(CH 2 ) n PPh 2 } 2 ] + [nido-7,8-R 2 -7,8-C 2 B 9 H 10 ] À (R = H, Me; n = 2 or 3) [5]. In the work that we now report, we have examined thermal replacement of PPh 3 ligands in the exo-nido ruthenium complex 1 with the (2S,4S)-(À)-2,4-bis-(diphenylphosphino)pentane (3,BDPP) and, as a result, three novel optically active 18-and 17-electron closo diphosphine-ruthenacarborane complexes have been obtained.…”
mentioning
confidence: 99%
“…Reaction of the ruthenium complex 1 with a 10% molar excess of diphosphine 3 in refluxing toluene for 1 h afforded a mixture of three ruthenacarborane products (4), (5) and (6) in ca. 54% (total content).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such an extension could, in principle, be accomplished by varying of either the phosphine ligands attached to the metal atom or the carborane cage substituents. For this reason, we have recently examined the room-temperature phosphine-diphosphine displacement reactions of 6, 2 6, 3 R = Me) using chelating diphosphines Ph 2 P(CH 2 ) 2 PPh 2 and Ph 2 P(CH 2 ) 3 PPh 2 [5] as well as thermal reaction of 1 with the chiral diphosphine (2S,4S)-(À)-2,4-bis(diphenylphosphino)pentane (3, S, S-bdpp) [6]. From the latter reaction, in refluxing toluene, a series of 18-and 17-electron closo-(S, S-bdpp)ruthenacarborane species were isolated, of which two were formulated as [closo-3,3-(S, S-bdpp)-3-Cl-3-H-3,1,2-RuC 2 B 9 H 11 ] (4) and [closo-3,3-(S, S-bdpp)-3-Cl-3,1,2-RuC 2 B 9 H 11 ] (5), and the third was ortho-cycloboronated derivative of 5, [closo-3-Cl-3,3-{(S, S)-Ph 2 PCH(CH 3 )CH 2 CH(CH 3 )PPh-ortho-C 6 H 4 }-3,1,2-RuC 2 B 9 H 10 ] (6).…”
Section: Introductionmentioning
confidence: 99%